“Everyone Enjoys a Siesta After Lunch in the West Indies”: Fictions of Labour and Languor - Dufoe, Nicole (Intermédialités / Intermediality)

(untitled) (Revue intermédialités, 2023)
This paper explores historical depictions of tourism in the West Indies, focusing on Frieda Cassin’s With Silent Tread, published in the 1890s and considered the first Antiguan novel. In both form and content, it exemplifies the commodification of the Caribbean as reprieve from the increasingly 24/7 demands of industrialized England, while attempting to elide the strenuous post-emancipation working conditions, chronic illness, and environmental exhaustion. The recurrent fictionalized image of the sleeping Black figure normalizes the rest in which the tourist temporarily indulges before returning, revived, to their imagined natural state of productivity—in 1890, and today. At the same time, rest becomes a potential act of resistance: rupturing the picturesque paradise.